2020
DOI: 10.12788/jhm.3372
|View full text |Cite
|
Sign up to set email alerts
|

Things We Do for No Reason: Routinely Prescribing Transfusion Premedication to Prevent Acute Transfusion Reactions

Abstract: Inspired by the ABIM Foundation's Choosing Wisely® campaign, the “Things We Do for No Reason™” series reviews practices that have become common parts of hospital care but which may provide little value to our patients. Practices reviewed in the TWDFNR series do not represent “black and white” conclusions or clinical practice standards, but are meant as a starting place for research and active discussions among hospitalists and patients. We invite you to be part of that discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…33,34 Despite this evidence, modern day reports of premedication continue to vary widely. 35 Furthermore an allergic predisposition as identified by atopic history and allergen-specific IgE levels in platelet transfusion recipients, but not donors, was significantly associated with allergic transfusion reaction. 29,36 Over two decades have passed since the initial trials by Heddle and colleagues of platelet component modifications and their impact on acute transfusion reaction rates.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…33,34 Despite this evidence, modern day reports of premedication continue to vary widely. 35 Furthermore an allergic predisposition as identified by atopic history and allergen-specific IgE levels in platelet transfusion recipients, but not donors, was significantly associated with allergic transfusion reaction. 29,36 Over two decades have passed since the initial trials by Heddle and colleagues of platelet component modifications and their impact on acute transfusion reaction rates.…”
mentioning
confidence: 93%
“…Subsequent double‐blind randomized controlled trials and a more recent systemic review and meta‐analysis showed no benefit for premedication even in a subgroup analysis of patients with a history of transfusion reaction 33,34 . Despite this evidence, modern day reports of premedication continue to vary widely 35 . Furthermore an allergic predisposition as identified by atopic history and allergen‐specific IgE levels in platelet transfusion recipients, but not donors, was significantly associated with allergic transfusion reaction 29,36 …”
mentioning
confidence: 99%